Practical applications of active mas dampers with hydraulic actuator. - Yamamoto, Masashi (Earthquake engineering & structural dynamics.)
The application of active mass damper (AMD) systems into buildings has been studied analytically and experimentally during the 1980s. The main purpose of these systems is to reduce the vibrations of buildings during strong winds or small earthquakes in order to improve the comfort of the building occupants. The authors have worked on the study and development of an AMD system using an electro servo type hydraulic actuator. First, the control technique of AMD with hydraulic actuator is formulated. Hydraulic actuators have an advantage of high durability and high cost performance, however, they also have non-linear dynamics, which makes their control difficult. Second, the applications of this system in the buildings are shown. The authors have applied this AMD system to four buildings in Japan. The outlines of these AMDs and buildings are described individually. To verify the control performance of the AMD in these buildings, free vibration tests were carried out just before their completion. Free vibration test results of each building demonstrated good control performance. After the completion, wind and earthquake observations were conducted. The records have shown a good performance of energy absorption of the vibration during wind excitation and small level earthquakes.